Changes in achilles tendon energy return and muscle energy cost following prolonged submaximal running in trained runners - Fletcher, J. R.; McIntosh, B. R. (International Calgary Running Symposium, August 14-17, 2014, 2014)
During prolonged running, the Achilles tendon (AT) demonstrates viscoelastic properties; the magnitude of AT length change may increase over time. Given the same AT force during running, additional lengthening should increase elastic energy return. However, AT elongation might also affect the magnitude of medial gastrocnemius (MG) muscle shortening. This additional muscle shortening would elevate the energy cost. Therefore, we aimed to quantify the elastic energy return and muscle energy cost to allow energy storage to occur prior to and following prolonged running. 14 Trained male (n=8) and female (n=6) distance runners (24±4 years, 1.72±0.09 m, 61±10 kg, . 65±6 ml/kg/min) ran 90 minutes (RUN) at approximately 85% of lactate threshold speed (sLT). Immediately prior to and following RUN, AT stiffness and running energy cost (Erun) at 85% sLT was determined. AT energy return was calculated from dynamometry and ultrasound. MG energy cost was estimated on the basis of AT force and crossbridge mechanics and energetics. Following RUN, AT stiffness was reduced from 332±116 N.mm-1 to 296±149 N.mm-1 (p<0.005). Erun increased from 4.56±0.32 J/kg/m to 4.62±0.32 J/kg/m (p<0.05). Estimated AT energy return increased (7.0±12.3 J.stride-1, p=0.06); however, MG muscle energy cost was also significantly elevated (9.7±5.7 J.stride-1, p<0.001), accounting for most of the post-RUN increase in Erun (8.4±14.1 J/stride). These results suggest a prolonged, submaximal run can significantly reduce AT stiffness and increase Erun in trained runners, possibly a result of elevated MG energy cost of shortening.